'Mountains of Israel': Fijians' Judaic Origins and the Use of the Old Testament in Highland Viti Levu. Issue 3 (7th October 2015) - Jones, Edwin
Abstract: The suggestion that the iTaukei (indigenous Fijians) are a lost tribe of Israel has gained currency among Methodists in the interior of Viti Levu, coexisting with a firm and widely held belief in the ancestors' emergence from the mystical Nakauvadra hills. For the people of Nabobuco, the Hebrew Bible's depiction of the relationship between Jehovah and the Israelites also contains powerful analogies with contemporary Christian experiences of collective sin and redemption. This paper discusses local genealogies and the use of the Old Testament to posit Nabobuco and Israel's moral equivalence within the Kingdom of God.